APPLIED ASPECTS OF GEOGRAPHICAL STUDIES OF TOURISM (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article discusses the practical-applied significance of geographical studies in terms of planning, organization and development of tourism. Particularly, the following directions of applied touristic-geographical studies were distinguished and discussed: planning and justification of touristic routes contents, development of certain types of tourism, provision of a complex destination approach, touristic-geographical marketing, organization of proportional territorial development of tourism, sustainable development of tourism. The emergence of a new, complex and interdisciplinary direction of geographical studies – applied tourist geography – is justified as well.
Keywords: touristic geography; applied touristic geography; geographical studies of tourism